Mechanical Properties and Fatigue Performance of 17-4 PH Stainless Steel Manufactured by Atomic Diffusion Additive Manufacturing Technology - Jon Rodriguez; Aitor Zuriarrain; Aitor Madariaga; Pedro J. Arrazola; Erika Dominguez; Itziar Fraile; Daniel Soler (Journal of Manufacturing and Materials Processing, 2023)
Additive Manufacturing (AM) is gaining importance as an alternative and complementary technology to conventional manufacturing processes. Among AM technologies, the Atomic Diffusion Additive Manufacturing (ADAM) technology is a novel extrusion-based process involving metallic filaments. In this work, the widely used 17-4 PH stainless steel filament was selected to study the effect of different deposition strategies of ADAM technology on mechanical properties. The printed parts had mechanical properties comparable to those obtained by other more developed AM technologies. In the case of tensile and fatigue tests, obtained values were in general greatly affected by deposition strategy, achieving better results in horizontal built orientation specimens. Interestingly, the effect was also considered of machining post-process (turning), which in the case of the tensile test had no remarkable effect, while in fatigue tests it led to an improvement in fatigue life of two to four times in the tested range of stresses.